P‐206L: Late‐News Poster: QVGA AMOLED Displays Using the Carbon Nanotube Enabled Vertical Organic Light Emitting Transistor. Issue 1 (May 2016) - McCarthy, Mitchell A.; Liu, Bo; Cheney, David J.; Lemaitre, Maxime G.; Jayaraman, Ramesh; Mativenga, Mallory; Geng, Di; Kim, Jeonggi; Kim, Hyo Min; Jang, Jin; Rinzler, Andrew G.
Abstract : We present the first display panels exploiting the nVerPix CN‐VOLET technology that reduces the pixel circuit of the conventional AMOLED display to two discrete components: the switching transistor and the CN‐VOLET. This permits high aperture ratio bottom emission displays—as high as 70% here— and greatly simplifies the manufacturing. Mono‐color QVGA AMOLED displays (6.4 cm diagonal) playing video will be shown.